2004
DOI: 10.1002/chem.200400543
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rhodium‐Catalyzed Reaction of Thiazolidine Derivatives with Carbodiimides

Abstract: A new, simple, and regioselective synthesis of thiazolidinimine derivatives based on the rhodium-catalyzed reaction of readily available thiazolidines with carbodiimides is described. This methodology provides direct access to a large variety of thiazolidinimine derivatives, possibly via a novel regiospecific insertion of carbodiimides into one of two ring carbon-nitrogen bonds, as well as a metal-catalyzed imine elimination process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Alper et al . have reported a rhodium‐catalyzed synthesis of thiazolidine using carbodiimides (Scheme 1b) [5] . But one of the most promising routes is the domino ring‐opening cyclization (DROC) of aziridines with isothiocyanates (Scheme 1c) [6] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alper et al . have reported a rhodium‐catalyzed synthesis of thiazolidine using carbodiimides (Scheme 1b) [5] . But one of the most promising routes is the domino ring‐opening cyclization (DROC) of aziridines with isothiocyanates (Scheme 1c) [6] .…”
Section: Methodsmentioning
confidence: 99%
“…[4] Alper et al have reported a rhodium-catalyzed synthesis of thiazolidine using carbodiimides (Scheme 1b). [5] But one of the most promising routes is the domino ring-opening cyclization (DROC) of aziridines with isothiocyanates (Scheme 1c). [6] This reaction requires the use of catalysts such as phosphines, [7] pyrrolidines, [8] palladium complex [9] or Lewis acid [10][11][12][13] to open aziridine ring.…”
mentioning
confidence: 99%
“…The metals involved in the insertion of carbodiimides into an M−C (M = metal) bond are main group, lanthanide, and early transition elements. Although carbodiimide insertion into the M−C bond of a late-transition-metal complex has been proposed as a mechanistic step, unambiguous evidence for such reactions has up until now not been available . Herein we report for the first time two types of carbodiimine reactivity toward a metal complex.…”
mentioning
confidence: 86%
“…Although carbodiimide insertion into the M-C bond of a late-transition-metal complex has been proposed as a mechanistic step, unambiguous evidence for such reactions has up until now not been available. 11 Herein we report for the first time two types of carbodiimine reactivity toward a metal complex. The first involves insertion of one of the CdN groups into the M-C bond and protonation of the other N. This process is related to one that we have just reported between a related palladium complex and nitriles, 12 except that protonation in the present case occurs at the uncoordinated nitrogen and that an additional different reaction also occurs.…”
mentioning
confidence: 93%
“…Considering the synthetic utility and immense biological activities, a large number of synthetic routes have been developed for the synthesis of 2-iminothiazolidines. The synthesis of 2-iminothiazolidines are reported from acylthioureas and allylic bromides via a base-mediated [3 + 2] annulation strategy, Fe­(III)-catalyzed [3 + 2] cycloaddition reaction of aziridines with heterocumulenes, organophosphine-catalyzed ring-opening reaction of activated aziridines with isothiocyanates, and Pd­(II)-catalyzed reaction of 1,2,3-trisubstituted aziridines with heterocumulenes, etc. A concise report by D’hooghe et al comprehensively describes various methodologies available for the synthesis of 2-iminothiazolidine derivatives, and as pointed out in their review, a general and direct method for the regio- and stereoselective synthesis of 2-iminothiazolidines bearing diverse substituents at the 2-, 3-, 4-, or 5-positions of the aza-heterocyclic moiety is greatly desirable.…”
Section: Introductionmentioning
confidence: 99%